REFUSAL TO PERFORM WORK NOT PROVIDED FOR IN THE EMPLOYMENT CONTRACT AS A FORM OF SELF-DEFENSE - Dostonbek Ruziyev; Javohir Qahramonov (European Science Publishing, 2025)
The article is devoted to the analysis of such concepts as “self-defense of the employee’s labor rights, implementation of ongoing reforms in this area, filling gaps in the legislation”, improvement of current legislative documents in this area, as well as increasing efficiency in the field of self-defense of the labor rights of employees using the latest information systems.
Keywords: Monthly salary, taxes and fees, severance pay, employment contract, self-defense, transfer to another job.